Polarizability of Rn-like Th4+ from spectroscopy of high-L Rydberg levels of Th3+ - Hanni, M. E.; Keele, Julie A.; Lundeen, S. R.; Fehrenbach, C. W. (My University, 2010)
Binding energies of high-L Rydberg levels of Th3+ were measured using the resonant excitation Stark ionization spectroscopy technique. Analysis of the data with the long-range polarization model leads to determination of dipole and quadrupole polarizabilities of the free Th4+ ion, αd = 7.61(6) a.u., αQ = 47(11) a.u.